2021
DOI: 10.1093/bioinformatics/btab822
|View full text |Cite|
|
Sign up to set email alerts
|

Automated classification of cytogenetic abnormalities in hematolymphoid neoplasms

Abstract: Motivation Algorithms for classifying chromosomes, like convolutional deep neural networks (CNNs), show promise to augment cytogeneticists’ workflows, however, a critical limitation is their inability to accurately classify various structural chromosomal abnormalities. In hematopathology, recurrent structural cytogenetic abnormalities herald diagnostic, prognostic, and therapeutic implications, but are laborious for expert cytogeneticists to identify. Non-recurrent cytogenetic abnormalities a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Considering the immense number of cells and potentially different malignant clones, this is a comparatively small number, which may not be representative of the entire sample. With the help of artificial intelligence (AI)-based programs, the time of analysis can be decreased and the number of analyzed metaphases increased [ 8 , 9 ]. Taken together, the method is nevertheless time consuming since a complete workup might require between 7 to 10 days under real-life conditions.…”
Section: Conventional Cytogenetic Procedures In Aml Diagnosismentioning
confidence: 99%
“…Considering the immense number of cells and potentially different malignant clones, this is a comparatively small number, which may not be representative of the entire sample. With the help of artificial intelligence (AI)-based programs, the time of analysis can be decreased and the number of analyzed metaphases increased [ 8 , 9 ]. Taken together, the method is nevertheless time consuming since a complete workup might require between 7 to 10 days under real-life conditions.…”
Section: Conventional Cytogenetic Procedures In Aml Diagnosismentioning
confidence: 99%
“…Because AI methods have been developed for visual pattern recognition in X‐rays, computed tomography scans, and stained tissue slices, one might predict that these methods could also be applied to the analysis of chromosomal karyotypes for constitutional rearrangements or to the analysis of tumor tissue for chromosomal rearrangements. To date, little to no AI appears to be used to routinely analyze chromosomal karyotypes for constitutional rearrangements (Tseng et al, 2023), although various efforts have been used to decipher chromosomal rearrangements in cancer specimens, such as from karyotyped hematologic malignancies (Bokhari et al, 2022; Cox et al, 2022; Vajen et al, 2022; Walter et al, 2021). As genomic analysis increasingly shifts toward molecular approaches, even for chromosomal disorders, AI methods are being developed to identify chromosomal deletions, duplications, and other types of rearrangements from NGS data directly (Lin et al, 2022; Popic et al, 2023).…”
Section: Deciphering Chromosomal Structural Variantsmentioning
confidence: 99%
“…Computer vision techniques have been applied to various chromosome-related tasks, such as chromosome segmentation, 2 chromosome classification, 3 chromosome generation, 4 trisomy detection, 5 translocation detection, 6 and the detection of structural abnormalities. 7 These studies have shown promising results and should contribute to improving the analysis of chromosomal images.…”
Section: Introductionmentioning
confidence: 97%